Hepatitis C Virus Infection in Patients with Beta Thalassemia after Multiple Transfusions at a Tertiary Care Hospital - Fareeha Naseer Syed, Nadia Kashif, Mubashir Razzaq Khan, Fayaz Ahmed Memon, Muhammad Zubair Jabbar, Sujith Kumar Palleti (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the prevalence of hepatitis C virus among patients of beta-thalassemia. Methods: We enrolled 200 patients of beta-thalassemia in this observational cross sectional study conducted at Department of Pathology, Jinnah Medical College/District Specialist Naseerullah Babar Memorial Hospital, Peshawar in the duration from March, 2022 to August, 2022. We determined the frequency of HCV in beta-thalassemia patients and assessed the association of HCV with age groups and number of blood transfusions. Chi Square test was used for association keeping P value at < 0.05 as statistically significant. Results: Patients’ average age recorded was 11.07±4.98 years. Male patients were 53.5% while the female patients were 46.5%. The frequency of HCV in our study was 37 (18.5%). HCV was significantly associated the number of blood transfusion < 7. Conclusion: Patients of beta-thalassemia are at higher risk of having. The frequency of hepatitis C virus in our study was 37 (18.5%). Keywords: Beta-thalassemia, Hepatitis C virus, Prevalence